The threat of Russia's force in Ukraine - Jankovic, Sava; Roeben, Volker (Journal on the use of force and international law, 2024)
In December 2021, Russia's military build-up near Ukraine, accompanied by explicit denials of any plans for an incursion, presents a significant case study on hidden threats of force. The Russian Representative to the United Nations argued that positioning military forces within its sovereign territory was a domestic matter and not a threat-an argument supported by China and uncontested by a few other member states (India, Ghana and Belarus). Such representations were presented despite the strong evidence of an impending invasion, including troop deployments along the Ukrainian border, strategic use of locations (such as Belarus) and medical personnel involvement. This case study raises important legal questions: how can threats of force, which violate the prohibition in Article 2(4) of the UN Charter, be more clearly identified? Furthermore, how can the international community improve its ability to censure such disguised or denied threats, as in Russia's case?